Manajemen Logistik Obat Antiretroviral Dalam Program Penanggulangan HIV/AIDS - Jegalus, Desiderata; Sirait, Rina Waty; Dodo, Dominirsep O.; Kendjam, Yoseph (Faculty of Public Health, Nusa Cendana University, 2019)
One of the points of the HIV AIDS prevention strategy is to increase the availability and affordability of antiretroviral treatment in hospitals or health centers. The emptiness in antiretroviral drugs is a phenomenon that commonly occurs in hospitals or health centers at the district or city level, and Manggarai Regency is one of the districts that experienced this condition from 2013 to 2017. The aim of this study is to explain the situation and the causes of the absence of antiretroviral drugs with a logistic management approach. This type of research is qualitative research. The informants of this study amounted to 8 people from RSUD dr. Ben Mboi, NTT Provincial Health Office, KPAP NTT and KPAD Manggarai. Data collection will take place from February to March 2018. The results are: Antiretroviral drug planning using consumption methods; budgeting and procurement of antiretroviral drugs by the Indonesian Ministry of Health; the storage of antiretroviral drugs is carried out according to the current standards for the storage of medicines; distribution of antiretroviral drugs from the provinces with expeditions and from hospitals to PLWHA with individual prescriptions that are represented by one person; the elimination of antiretroviral drugs was never performed; control of antiretroviral drugs that are adapted to the schedule of taking medication; cause of the absence of antiretroviral drugs due to the lack of specialized staff administering antiretroviral drugs in hospital pharmacies. Management of antiretroviral drugs in Manggarai Regency runs accordingly the logistics management cycle, but there are still some issues that accompany this process. Issues in question include insufficient human resources in terms of quantity and quality, non-procedural implementation and a weak coordination system. It is recommended that improvements be made to the logistical management process of antiretroviral drugs in hospitals, as well as strengthening the coordination and evaluation system of all parties involved in the logistics management of antiretroviral drugs.